STRATEGI PUBLIC RELATIONS PTPN RADIO SOLOUNTUK MENINGKATKAN BRAND AWARENESSDENGAN MENJADI MEDIA PARTNER EVENT - Chantyka Putri Nugraheni (Solidaritas, 2025)
Radio is an electronic medium for conveying messages via electromagnetic waves. PTPN Radio Solo is a radio that has existed in the city of Solo since 1968. Even though internet-based media now appears, PTPN Radio Solo continues to survive and adapt to technological developments. In the digital era, radio not only competes with fellow radio stations but also with online media. PTPN Radio Solo experienced a decline in brand awareness among event workers during the pandemic until early 2022. Public relations at PTPN Radio Solo played a very important role in increasing brand awareness. Therefore, PTPN Radio Solo has become an event media partner to increase brand awareness among event workers. In 2023, PTPN Radio Solo's brand awareness will increase by becoming a media partner for the event. The purpose of this research is to determine PTPN Radio Solo's public relations strategy to increase brand awareness by becoming a media partner for events. This type of research is descriptive qualitative. Data collection techniques through interviews, observation and documentation. The analysis was carried out using the Three Ways Strategy theory (Push, Pull, and Pass) according to Thomas L. Hariss. The results of this research are that PTPN Radio Solo, when it became a media partner for the event, carried out a push strategy in the form of trade publicity, publication of pamphlets, live reports, and video recaps on social media and advertisements on radio. PTPN Radio Solo is also implementing a pull strategy in the form of publishing creative content. Meanwhile, the pass strategy carried out by PTPN Radio Solo is to create collaborative content or content accompanied by mentions of event organizers, guest stars and other media partners at the event. The research results show that the push, pull and pass strategy carried out by PTPN Radio Solo can increase brand awareness among event organizers. Keywords: Strategy, public relations, radio, brand awareness, media partner event.